2019
DOI: 10.3389/fcell.2019.00107
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Cell Migration, Invasion, and Adhesion Assays: From Cell Imaging to Data Analysis

Abstract: Cell migration is a key procedure involved in many biological processes including embryological development, tissue formation, immune defense or inflammation, and cancer progression. How physical, chemical, and molecular aspects can affect cell motility is a challenge to understand migratory cells behavior. In vitro assays are excellent approaches to extrapolate to in vivo situations and study live cells behavior. Here we present four in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
262
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 380 publications
(297 citation statements)
references
References 24 publications
2
262
0
2
Order By: Relevance
“…To minimize the risk of phototoxicity, we restricted image acquisition of the fluorescent mTurquoise2 channel for our transfected cells to the last frame alone. We utilized a similar individual cell tracking data analysis approach as described in (Pijuan et al ., 2019). Cell motility was tracked using the manual tracking function in ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“…To minimize the risk of phototoxicity, we restricted image acquisition of the fluorescent mTurquoise2 channel for our transfected cells to the last frame alone. We utilized a similar individual cell tracking data analysis approach as described in (Pijuan et al ., 2019). Cell motility was tracked using the manual tracking function in ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“…Maiques and co-workers assessed the effect of TTCC blockers on the migration and invasion of melanoma cells using wound-healing, single-cell, and transwell assays [66]. We showed that TTCC blockers reduce the migration rates and invasive potential of BRAF V600E -mutant melanoma cells due to autophagy inhibition, with no significant effect in NRAS-mutant melanoma cells ( Table 1; Figure 2) [20,66]. Melanoma cell invasion and subsequent metastasis are hallmarks of melanoma dissemination [67].…”
Section: Migration and Invasionmentioning
confidence: 97%
“…The lower chamber was lled with 600 μl of 1640 medium supplemented with 20% FBS. After 24 hours of incubation at 37°C with 5%CO 2 , cells remaining in the upper membrane surface were removed with a cotton swab, whereas invaded cells were xed and stained with 0.5% crystal violet [8].…”
Section: Transwell Assaymentioning
confidence: 99%